Indoor air quality and atopic sensitization in primary schools: A follow-up study - Rufo, JP (2016)
Background The onset and exacerbation of allergic diseases and asthma have been associated with poor indoor air quality (IAQ) inside classrooms. Objective The aim was to investigate how IAQ changed in primary schools after applying indoor air quality recommendations, and to explore how these changes influenced allergic sensitization on children. Methods Total volatile organic compounds, PM2.5, PM10, CO2, CO, temperature and relative humidity in the indoor and outdoor air of 20 primary schools were measured in 2010–2012. The school staff received instructions on how to improve IAQ in accordance with the dedicated guidelines. Atopy status was assessed in children attending the participating classrooms by skin prick tests and exhaled nitric oxide. A follow-up sampling campaign was performed in 2014–2015 in the same schools. Results Indoor PM2.5 and PM10 concentrations were approximately 40% lower in the follow-up measurements (p < 0.05). There were no significant differences regarding outdoor PM concentrations. Nevertheless, PM levels from the follow-up campaign still exceeded the reference value established by Portuguese legislation. Moreover, there were no significant differences in atopic prevalence and FENO values between the campaigns. Conclusion These findings suggest that adoption of the recommendations based on the SINPHONIE guidelines was particularly successful in reducing PM2.5 and PM10 in primary schools of Porto. Nevertheless, the schools failed to reduce the levels of other IAQ pollutants, as well as the prevalence of atopic disease.